Analisis Ekspresi Kekuasaan dalam Kantor Desa Replika Istana Kepresidenan di Jawa Timur - Shafira Zulfa Audina; Bambang Soemardiono; Muhammad Faqih (Universitas Sebelas Maret Surakarta, 2024)
Architectural activities of rural communities in Indonesia are closely related to local culture and traditions. As part of folk architecture, this activity has led to the phenomenon of village offices replicating the Presidential Palace. This research explores the intentions of the designers of Dadapan Village Office and Kemuningsari Kidul Village Office as replicas of the Presidential Palace to find out the expression of power that they want to communicate. This research uses qualitative methods with the tactics of field observation, in-depth interviews, and literature studies. Dadapan Village Office located in Pacitan Regency has a more complex expression of power than Kemuningsari Kidul Village Office located in Jember Regency. The expression of power intended by the designer of the village office includes the desire to form an identity; as a symbol of splendor; a symbol of wealth; a symbol of authority; a symbol of pride; and a symbol of a community protector.